Direct synthesis of C-glycosides from unprotected 2-N-acyl-aldohexoses via aldol condensation–oxa-Michael reactions with unactivated ketones. Issue 1 (13th November 2015) - Johnson, Sherida; Tanaka, Fujie
Abstract : C-glycosides were synthesized from unprotected 2- N -acyl-aldohexoses and unactivated ketones in one pot via aldol condensation–oxa-Michael reactions. Abstract : C-glycosides are important compounds as they are used as bioactive molecules and building blocks. We have developed methods to concisely synthesize C-glycosides from unprotected 2- N -acyl-aldohexoses and unactivated ketones; we designed aldol-condensation–oxa-Michael addition reactions catalyzed by amine-based catalysts using additives. Depending on the conditions used, C-glycosides were stereoselectively obtained. Our methods allowed the C–C bond formations at the anomeric centers of unprotected carbohydrates under mild conditions to lead the C-glycosides in atom- and step-economical ways.